2021
DOI: 10.1111/pirs.12572
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of the impacts of large‐scale urban projects on land values: The case of Belo Horizonte, Brazil

Abstract: Large‐scale urban projects (LSUPs) are capable of changing cities' structures and, consequently, have a potential deep impact on land values. However, to assume that the LSUP always uplift land values may dismiss too quickly some key aspects of these investments. This work uses a difference‐in‐differences model to assess the impacts of LSUPs on land values, implemented in Belo Horizonte, Brazil. Results indicate that the impacts of LSUPs vary according to the kind of project (transit, iconic building and retai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 50 publications
(80 reference statements)
0
4
0
Order By: Relevance
“…Indeed, the study area faced significant land value increases after the development policy, showing reinvestment in fixed capital. Almeida et al (2021), using a difference-in-difference regression model, found statistically significant land value increases related to these investments. We then identified the land users in the study area and whether they had changed.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Indeed, the study area faced significant land value increases after the development policy, showing reinvestment in fixed capital. Almeida et al (2021), using a difference-in-difference regression model, found statistically significant land value increases related to these investments. We then identified the land users in the study area and whether they had changed.…”
Section: Resultsmentioning
confidence: 97%
“…To assess the policy's effect on land values, we used information from Belo Horizonte's land transfer tax databases from 2009 to 2017 (Almeida et al, 2021). It is worth noting that property taxes had a stable growth in the neighbourhoods under study as well as in entire municipalities, being adjusted by only the inflation rate.…”
Section: Data and Approachmentioning
confidence: 99%
“…Infrastructure quality, access to services like public healthcare and education, and security measures such as the presence of police stations all impact the desirability of a neighborhood and, consequently, its land values. Cities that embark on large-scale urban projects, as recently witnessed in Dubai and Doha, are likely to see a huge positive change in land values (Almeida et al, 2021). Factors like flooding risk, noise pollution, waste management, and the quality of roads and transportation routes can either accentuate or attenuate the attractiveness of an area, directly affecting land prices (Aziz et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…However, public financing tools, even debt-based instruments, can inadvertently increase surrounding (private) property values. Almeida et al (2021) use fiscal geographies to understand how the state could recover increased property prices due to public expenditure through a mechanism called value capture. Wijburg (2021) considers taxes and other fiscal instruments as critical levers for “de-financializing” housing.…”
Section: Property Environment and Financementioning
confidence: 99%